Hubungan Harga dengan Keputusan Pembelian Aki pada Toko Rn Accu di Punggur, Lampung Tengah - Iryantoro, Lambet (Universitas Muhammadiyah Metro, 2021)
Based on the results of the pre-survey, what became a phenomenon in this study was that there was an imbalance between the sale of batteries at high prices and batteries at medium and low prices. In connection with these problems, the formulation of the problem in this study is